A formação e a autoformação de professores de matemática : implicações na prática pedagógica - Oliveira, Edmilson de (2016)
This study aimed to analyze the training and self-training of mathematics teachers and the implications for their teaching practice. The subjects of research ten teachers of Mathematics of public schools in Porto Alegre, Rio Grande do Sul. As data collection instruments were used semi-structured questionnaire and observations of teaching practice these teachers. The answers given by teachers were analyzed qualitatively using the method of Textual Analysis Discourse, relating them to issues observed in the classroom. The theoretical contributions that were the basis for this research were authors such as Tardif (2014), Shulman (1986; 2014), Nóvoa (1997), Libâneo (2013), among others. To support the analysis were used mainly the results of studies Shulman (1986) and Tardif (2014) and his contributions on the categorization of the different types of knowledge and teacher's knowledge. The data analysis part of four priori categories, either: teachers' perceptions of analysis about planning a math class; perceptions of teachers about the skills needed for the preparation of a math class; perceptions of teachers about the knowledge that has to prepare a math class; knowledge and actions generated in the self-training of mathematics teachers. From these categories was possible to outline the issues related to data collected from which emerged the intermediate categories. It can be argued that the pedagogical content knowledge in daily practice of the teacher is essential. One way to apply this knowledge is inserting it in the curricula of undergraduate programs. Another means is the self-training as a daily practice to remedy the lack of this knowledge in the degree courses. In the analysis we realized the lack of strategic knowledge (SHULMAN, 1986), by teachers. Such knowledge gives teachers the ability to act effectively, relating and articulating the skills to prepare math classes with the prior knowledge of students as well as their realities.